Comparing the classification performance of multi sensor data fusion based on feature extraction and feature selection - Maz Jamilah, Masnan; Ali Yeon, Md Shakaff, Prof. Dr.; Ammar, Zakaria; Nor Idayu, Mahat (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.